2022
DOI: 10.1093/ajcn/nqac085
|View full text |Cite
|
Sign up to set email alerts
|

The effects of SCFAs on glycemic control in humans: a systematic review and meta-analysis

Abstract: Background Non-communicable disease development is related to impairments in glycaemic and insulinemic response, which can be modulated by fiber intake. Fiber's beneficial effect upon metabolic health can be partially attributed to the production of short-chain fatty acids (SCFAs) via microbial fermentation of fiber in the gastrointestinal tract. Objective We aimed to determine the effect of the SCFAs, acetate, propionate, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…In contrast, some studies have shown that propionic acid improves islet β cell function, regulates insulin secretion [33], reduces digestibility by inhibiting amylase activity [34] and delays gastric emptying and glucose absorption from the diet [35,36], all of which maintain blood glucose balance. Furthermore, a meta-analysis showed that acute or chronic propionate interventions had no significant effect on fasting glycaemia or fasting insulin, postprandial glucose or postprandial insulin levels [37]. In addition, propionate also has a crucial effect on body weight.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, some studies have shown that propionic acid improves islet β cell function, regulates insulin secretion [33], reduces digestibility by inhibiting amylase activity [34] and delays gastric emptying and glucose absorption from the diet [35,36], all of which maintain blood glucose balance. Furthermore, a meta-analysis showed that acute or chronic propionate interventions had no significant effect on fasting glycaemia or fasting insulin, postprandial glucose or postprandial insulin levels [37]. In addition, propionate also has a crucial effect on body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Ruminococcus is also a potential producer of SCFAs ( 53 ). Numerous pieces of evidence indicated that SCFAs play a fundamental role in gut microbial homeostasis and host metabolism ( 54 , 55 ). Furthermore, SCFAs were also involved in the regulation of intestinal permeability, immunologic function, and cell proliferation ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been no reports of any adverse side effects of SCFAs on human health. A very recent systematic review and meta-analysis assessed the effects of acute and chronic administration of SCFAs and vinegar on glycemic control 71 . Interestingly, they did not observe a significant effect of acute acetate and propionate as well as chronic propionate treatment on glucose and insulin concentrations.…”
Section: Discussionmentioning
confidence: 99%